THE INFLUENCE OF MANAGEMENT CONTROL SYSTEMS ON EMPLOYEE PERFORMANCE - Zulkarnaen, Wandy (LPPM STIE Muhammadiah Bandung, 2023)
The aim of this research is to analyze the influence of the management control system on employee performance at PT. Trimitra Dinamika Consultants . This type of research is quantitative research and the data source is primary data with questionnaires. The sample in this research were employees of PT. Trimitra Dinamika Consultants . The data analysis methods in this research are descriptive statistics, characteristic data, simple validation and regression analysis using a significance level of 5%, and tested using path analysis. The data processing method uses SPSS 23.0 For Windows software. Based on the results of the analysis, it is known that the management system has a positive and significant effect on employee performance at PT. Trimitra Dinamika Consultants .